Study of Crack Generation and Expansion Behavior of Frame-Supported Float Glass after Heat Exposure - Yanni Zhang; Luoxin Huang; Jun Deng; Zhichao Feng; Dan Yang; Xuemeng Liu; Shuai Zhang (Fire, 2023)
Float glass installed with frame supports is broadly exploited in building construction. In a fire environment, the breakage of float glass significantly influences the dynamic development of the fire within the building space. The thermal rupture behavior of the frame-supported float glass subjected to thermal loading is carefully examined using a self-built experimental system. The designed system is aimed at capturing crucial behavioral parameters. The experimental study reveals that the main reason for the breakage of the frame-supported float glass is the temperature difference on the glass surface, with a critical temperature difference of approximately 65 °C. The crack starts at the edge of the glass surface where the temperature difference is maximum and then rapidly expands. By intersecting the cracks, a crack island is configured, which is not dislodged under the stress of the supporting frame and the surrounding glass. A thermomechanical and micro-geometric model of the frame-supported float glass is developed based on the PFC2D program to show further the micro-crack expansion pattern of the frame-supported float glass under thermal loading. This scrutiny provides theoretical guidance for installing and using frame-supported float glass in construction projects and identifying fire evidence.